2020
DOI: 10.3389/fpls.2020.01288
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Expression of Bud Dormancy-Associated MADS-Box Genes (DAM) in European Plum

Abstract: Bud dormancy in temperate perennials ensures the survival of growing meristems under the harsh environmental conditions of autumn and winter, and facilitates an optimal growth and development resumption in the spring. Although the molecular pathways controlling the dormancy process are still unclear, DORMANCY-ASSOCIATED MADS-BOX genes (DAM) have emerged as key regulators of the dormancy cycle in different species. In the present study, we have characterized the orthologs of DAM genes in European plum (Prunus d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 107 publications
(175 reference statements)
2
22
0
Order By: Relevance
“…As suggested before (Jiménez et al, 2009;Li et al, 2009), posterior subfunctionalization and/or neofunctionalization may have resulted in their actual function. The clustering of the DAM orthologs in two major clades, namely DAM1, -2, and -3; and DAM4, -5, and -6, as previously observed (Prudencio et al, 2018;Balogh et al, 2019;Quesada-Traver et al, 2020;Wang et al, 2020), agrees with previous transcriptomic studies of DAM genes in peach and Japanese apricot, in which two different expression patterns have been observed for the two groups of genes. DAM1, -2, and -3 have a maximum expression during bud set, while DAM4, -5, and -6 show maximum expression when chilling requirement are satisfied (Falavigna et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…As suggested before (Jiménez et al, 2009;Li et al, 2009), posterior subfunctionalization and/or neofunctionalization may have resulted in their actual function. The clustering of the DAM orthologs in two major clades, namely DAM1, -2, and -3; and DAM4, -5, and -6, as previously observed (Prudencio et al, 2018;Balogh et al, 2019;Quesada-Traver et al, 2020;Wang et al, 2020), agrees with previous transcriptomic studies of DAM genes in peach and Japanese apricot, in which two different expression patterns have been observed for the two groups of genes. DAM1, -2, and -3 have a maximum expression during bud set, while DAM4, -5, and -6 show maximum expression when chilling requirement are satisfied (Falavigna et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…The amino acid sequence of PavDAMs recently predicted in 'Royal Lee' and 'Hongdeng' cultivars (Wang et al, 2020) is highly similar to that reported in this work for the 'Regina' genome (99.0 and 99.9%, respectively). The sequence of each PavDAM reported in this work includes the four characteristic domains of MIKC type II MADS-box, as reported earlier in peach, Japanese apricot, or plum (Jiménez et al, 2009;Xu et al, 2014;Quesada-Traver et al, 2020). Furthermore, we observed in this study, that each PavDAM comprises eight exons making the genomic structure of the six genes very similar to that of the DAM genes previously reported in other Prunus species, namely peach, Japanese apricot, European plum (Jiménez et al, 2009;Sasaki et al, 2011;Quesada-Traver et al, 2020).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations